Chitosan based fiber-optic Fabry–Perot humidity sensor - Chen, Li Han (2013)
A relative humidity fiber sensor based on Fabry–Perot interferometry configuration is presented. The proposed fiber sensor is functionalized with a thin layer of a moisture-sensitive natural polymer chitosan to form a low fineness Fabry–Perot sensor. The sensing scheme used in this work is based on the swelling effect of chitosan sensing film (degree of swelling varies as a function of relative humidity) which will induce optical path modulation when relative humidity is changed. As observed, the proposed sensor exhibits a sensitivity of 0.13 nm/%RH for relative humidity ranging from 20%RH to 95%RH with a RH uncertainty of ±1.68%RH and fast response time of 380 ms.